2019
DOI: 10.1038/s41598-019-53265-4
|View full text |Cite
|
Sign up to set email alerts
|

Success rates in isolating mesenchymal stem cells from permanent and deciduous teeth

Abstract: Stem cells from human exfoliated deciduous teeth (SHED) and human dental pulp stem cells (hDPSCs) have emerged as attractive cell sources for bone regeneration. However, the specific teeth and the conditions most suitable for stem cell isolation remain unclear. Therefore, the success rate of SHED and hDPSCs isolation, the patient age and remaining root length in deciduous teeth were evaluated. Successful isolation was defined as when the cell culture was maintained up to the third passage without any contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…For instance, Biebak et al [ 28 ] optimized the protocols to increase the isolation yield of umbilical cord blood MSCs (UCB-MSCs) up to 63%, while BMSCs were used as a positive control (success rate 100%). Nakajima et al [ 22 ] investigated the success rate of isolating DPSCs and SHED, reporting 70% and 82%, respectively. Neither of these studies harvested the two cell types from the same donor, most probably owing to the apparent difficulty in collecting cells from two different sites within the same patient, and hence derives the relevance of the protocol proposed in the present work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Biebak et al [ 28 ] optimized the protocols to increase the isolation yield of umbilical cord blood MSCs (UCB-MSCs) up to 63%, while BMSCs were used as a positive control (success rate 100%). Nakajima et al [ 22 ] investigated the success rate of isolating DPSCs and SHED, reporting 70% and 82%, respectively. Neither of these studies harvested the two cell types from the same donor, most probably owing to the apparent difficulty in collecting cells from two different sites within the same patient, and hence derives the relevance of the protocol proposed in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…According to the protocol described by Nakajima et al [ 22 ], successful isolation was defined when the cell culture reached the third passage (P3) without any contamination. Cells were observed daily under an optical microscope until the day when cell adhesion was observed, and colonies were formed.…”
Section: Methodsmentioning
confidence: 99%
“…In agreement with 6). In addition, other related factors, such as the patient's age, length of the remaining root, and mechanical stress influence the successful isolation and establishment of SHEDs (17). SHEDs from both groups in established cultures displayed a similar, characteristic spindle-shaped, fibroblastlike morphology.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the pulp acquired from deciduous teeth without root resorption did not support the derivation of viable cell lines in comparison to those from teeth with resorbed roots (15). Although the detailed biological properties of SHED are being rigorously investigated (5,16,17), the effect of different levels of root resorption on the characteristics of cell lines obtained from these teeth remains inconclusive. Thus, the tooth source that is most suitable for the isolation of SHEDs needs to be determined.…”
Section: Dental Pulp Stem Cells (Dpscs) From Impacted Third Molarsmentioning
confidence: 99%
“…Human dental pulp stem cells and SHED are obtained non-invasively, reducing the physical burden on patients, and these cells have the same regenerative ability as BMSCs [17][18][19][20] . However, transplantation of BMSCs does not result in signi cantly higher bone regeneration compared to autogenous bone graft 21,22 .…”
Section: Discussionmentioning
confidence: 99%